Provably secure authenticated content key distribution framework for IoT-enabled enterprise digital rights management systems. (12th March 2021) - Rana, Saurabh; Mishra, Dheerendra
The internet of things (IoT) is one of the fastest growing technology, which is helping the enterprise industry. However, it brings greater challenges to privacy and security. Moreover, online piracy of content is an emerging issue. Thus, authorised content access is required. Enterprise digital rights management (E-DRM) systems aim to manage the access of electronic records necessitates establishing a standard set of access requirements, binding those access requirements to the electronic records, and computing the permission criteria. In this chain of control, efficient authenticated access to electronic documents is a crucial task. To address the issues, a protocol is designed. Security of the proposed scheme is proved in the random oracle model. Validation of security is done using 'Automated Validation of Internet Security Protocols and Applications (AVISPA)', which indicates that the protocol is safe. Moreover, the comparative study shows that it has a desirable attribute of efficiency.